The Economic Impact of a Foot‐and‐Mouth Disease Outbreak for Ontario's Beef Sector. (4th September 2016) - Cairns, Alexander; Tolhurst, Tor; Poon, Kenneth; Ker, Alan P.; Duff, Stephen; Jacques, David; Yang, Lin
Abstract : Biosecurity is an increasingly prominent concern to the Canadian agri‐food sector given heightened public awareness of animal welfare and the continued importance of trade. Due to the potential for large‐scale animal depopulation and uncertain trade flow restrictions, the economic costs and animal welfare implications of disease outbreaks have prompted efforts to control their spread within and across trade boundaries. We build a partial equilibrium model of the beef supply chain in Ontario to examine the welfare impacts of a foot‐and‐mouth disease outbreak inside and outside the province. Somewhat surprisingly, economic impacts for Ontario are not dramatically different between an outbreak within the province versus an outbreak in western Canada: losses total 245 and 217 million, respectively. When the outbreak occurs outside Ontario and provincial zoning is recognized, losses total only 93 million. Restrictions on international and, inter‐ and intra‐provincial movement of livestock and beef products are the main driver of losses. A strength of our model is that we are able to disaggregate these impacts across the various market participants (i.e., producers, processors, retailers, consumers). Retailers and consumers incur little to no losses as imports from the United States easily fill shortages in supply. Production losses from livestock movement restrictions and depopulation are partially offset by higher prices, while processors bear the brunt of the losses due to reduced supply and higher livestock prices. La biosécurité revêt de plus en plus d'importance dans le secteur agroalimentaire canadien en raison de la sensibilisation accrue du public au bien‐être animal et de l'importance soutenue du commerce. Compte tenu de l'éventualité d'un dépeuplement animal à grande échelle et de mesures pouvant restreindre le flux des échanges commerciaux, le coût économique des éclosions de maladies et leurs répercussions sur le bien‐être animal ont stimulé les efforts afin de maîtriser leur propagation tant à l'intérieur qu'à l'extérieur des frontières commerciales. Dans la présente étude, nous avons élaboré un modèle d'équilibre partiel de la chaîne d'approvisionnement du bœuf en Ontario afin d'examiner les répercussions d'une éclosion de fièvre aphteuse à l'intérieur et à l'extérieur de la province. Étonnamment, que l'éclosion survienne en Ontario ou dans l'Ouest canadien, l'impact économique pour l'Ontario ne diffère pas considérablement : les pertes totales étant de 293 millions de dollars (M) et de 267 M respectivement. Lorsque l'éclosion survient à l'extérieur de l'Ontario et que les zones de contrôle provinciales sont déterminées, les pertes totales s'élèvent à 27 M seulement. Les restrictions concernant le déplacement du bétail et des produits de bœuf entre pays, entre provinces et à l'intérieur d'une même province constituent les principaux facteurs entrainant des pertes. L'une des forces de notre modèle tient au fait que nous avons été en mesure de désagréger les impacts entre les différents acteurs dans le marché (producteurs, transformateurs, détaillants et consommateurs). Les détaillants et les consommateurs subissent peu ou pas de pertes étant donné que les importations en provenance des États‐Unis comblent facilement les pénuries de l'offre. Du côté des producteurs, les pertes causées par le déplacement et le dépeuplement du bétail sont en partie contrebalancées par des prix élevés, tandis que les transformateurs essuient les pertes les plus lourdes en raison d'une diminution de l'offre et du prix du bétail élevé.